2014
DOI: 10.1590/1983-084x/12_115
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e atividade in vitro de três óleos essenciais sobre Colletotrichum gloeosporioides do maracujazeiro

Abstract: RESUMO:Objetivou-se avaliar a ação de diferentes concentrações de óleos essenciais de três plantas medicinais sobre o crescimento micelial, a produção e a germinação de conídios de Colletotrichum gloeosporioides (Penz.). Utilizou-se os óleos essenciais de Lippia sidoides Cham., Cymbopogon citratus (DC) Stapf.) e Ocimum gratissimum L. em cinco concentrações (0 µL mL -1 , 1 µL mL -1 , 3 µL mL -1 , 5 µL mL -1 e 7 µL mL -1 ) com 4 repetições no delineamento inteiramente casualizado, em esquema fatorial 5x3. Os óle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
9
1
7
Order By: Relevance
“…The authors [23] also observed similar percentages for Geranial (46.3%) and Neral (31.28%). Yet [24] found levels of 43.6% for Neral and 34% for Geranial, values that are different to the ones found on this work, where the highest percentage was of Neral. It is known that many factors, such as extraction method, access and conditions of cultivation may have an influence on the levels of the essential oil components.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors [23] also observed similar percentages for Geranial (46.3%) and Neral (31.28%). Yet [24] found levels of 43.6% for Neral and 34% for Geranial, values that are different to the ones found on this work, where the highest percentage was of Neral. It is known that many factors, such as extraction method, access and conditions of cultivation may have an influence on the levels of the essential oil components.…”
Section: Discussioncontrasting
confidence: 99%
“…At the center of each plate a 5-mm diameter disk was placed with mycelium of the monosporic culture grown prior for 7 days in PDA. The plates were then incubated at 25°C (AQUINO et al, 2014). Estimations were conducted through daily measurements of the colony diameters until day ten, after which, the Mycelial Growth Index (MGI) was determined, applying the equation adopted by ABREU et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Trabalhos têm demonstrado o potencial dos óleos essenciais no controle de fungos fitopatogênicos como Alternaria solani, Penicilium digitatum, Colletotrichum musae, Corynespora cassiicola, Macrophomina phaseolina, Sclerotinia sclerotiorum, Alternaria alternata, Pseudocercospora griseola, dentre outros (Balbi-peña et al, 2006;Almeida et al, 2006;Abdolahi et al, 2010;Carlos et al, 2010;Martins et al, 2010;Hojos et al, 2012).…”
Section: Introductionunclassified